2017
DOI: 10.1111/imm.12852
|View full text |Cite
|
Sign up to set email alerts
|

Urban particulate matter stimulation of human dendritic cells enhances priming of naive CD8 T lymphocytes

Abstract: SummaryEpidemiological studies have consistently shown associations between elevated concentrations of urban particulate matter (UPM) air pollution and exacerbations of asthma and chronic obstructive pulmonary disease, which are both associated with viral respiratory infections. The effects of UPM on dendritic cell (DC) ‐stimulated CD4 T lymphocytes have been investigated previously, but little work has focused on CD8 T‐lymphocyte responses despite their importance in anti‐viral immunity. To address this, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…223 Myeloid dendritic cells exposed to urban PM enhanced naive CD8 + T cell priming, resulting in increased secretion of granyzme A and B. 224 Increased production of proinflammatory cytokines by CD8 + T cells responding to a viral infection could result in damage to bystander cells and inflammation amplification.…”
Section: Effects Of Pollutant Exposure On Adaptive Immune Responsesmentioning
confidence: 99%
“…223 Myeloid dendritic cells exposed to urban PM enhanced naive CD8 + T cell priming, resulting in increased secretion of granyzme A and B. 224 Increased production of proinflammatory cytokines by CD8 + T cells responding to a viral infection could result in damage to bystander cells and inflammation amplification.…”
Section: Effects Of Pollutant Exposure On Adaptive Immune Responsesmentioning
confidence: 99%
“…Likewise, IL-33 potently enhances antiviral CD8 + T-cell responses [87]. An association of CD8 + cells with cigarette use [56] suggests that smoke may also activate CD8 + cells, while Tc2 cells in both mice and humans express perforin and granzyme [88] and induction of granzyme A mRNA and protein have been demonstrated in response to diesel fume particulates in human bronchoscopy samples [89].…”
Section: Activation Of Cd8 + T-cellsmentioning
confidence: 99%
“…The capacity of pollutants to stimulate DC maturation is not limited to PM since Alexis et al reported increased expression of CD80 in response to either LPS or ozone [16,17]. Most recently Pfeffer et al reported increased expression of CD83 (an alternative maturation marker) and subsequent enhanced priming of CD8 T lymphocytes by ultrafine PM exposed human DCs [18].…”
Section: Introductionmentioning
confidence: 99%